Penerapan Sistem Informasi Geografis Dalam Pemetaan Toko Oleh - Oleh Khas Lombok - Putra, Yupi Kuspandi; Hidayat, Muh. Adrian Juniarta; Sadali, Muhamad; Mahpuz, Mahpuz; Aropah, Muhamad Guruh (Infotek: Jurnal Informatika dan Teknologi, 2024)
This research aims to produce a geographic information system with spatial data visualization containing the location of East Lombok souvenir shops, shop information and directions that will be presented to visitors or users. The research targets were carried out in several sub-districts in the East Lombok Regency area which have souvenir shops. This is an effort to introduce craft products and food and drinks that are characteristic of the East Lombok Regency area. The data used in this research is by collecting map data of the East Lombok Regency area using Google Map API and Google Map Direction Service, interviews with shop owners, data collection on coordinate points and several other supporting data. The result of this research is that a web-based geographic information system for East Lombok souvenir shops has been built using the Google Maps API which makes it easy for web users to find out the position of East Lombok souvenir shops, where there is shop information and shop position. , items for sale and directions to the desired store.